COVID‐19 and emergency care for adults experiencing homelessness. (3rd October 2020) - Miller, Jean‐Philippe; Phillips, Georgina; Hutton, Jennie; Mackelprang, Jessica L; O'Reilly, Gerard M; Mitchell, Rob D; Smith, Cathie; Mitra, Biswadev
Abstract: Homeless individuals face many barriers to accessing healthcare, and EDs are often their primary entry point to the healthcare system. The COVID‐19 pandemic has the potential to exacerbate existing social inequities and health disparities, including barriers to accessing social services and healthcare. Addressing the complex social and chronic health issues associated with homelessness can be challenging within the acute care environment. This perspective reflects upon the delivery of emergency healthcare to patients experiencing homelessness, and highlights strategies for optimising health outcomes during and beyond the pandemic.